Production, characterization and assessment of sludge-derived biochar for water treatment as a sustainable solution towards a circular economy - Frota, André Madson Araújo (2023)
Due to increasing population growth and increased pollution of water bodies, problems related to eutrophication have become more common around the world. Cyanobacteria blooms – organisms capable of releasing cyanotoxins harmful to aquatic ecosystems and human health – are a risk associated with this phenomenon. One of the technologies commonly used to remove these contaminants is activated carbon. However, its use makes the water treatment process more expensive and increases the production of sludge in water treatment plants (WTPs), so this practice can become unfeasible from an economic and environmental point of view. A promising material for adsorption in aqueous media is biochar. Initially, in the first part of this research, it was found through a systematic review that properties such as surface area, when considered alone, are not a good indicator of adsorption capacity. It is necessary to evaluate a combination of adsorbate, adsorbent and aqueous solution properties for the correct selection of PAC or biochar. Overall, although activated carbon has been widely used for cyanotoxin removal, not enough data are available, and few studies have been performed for different toxins, as most focus on MC-LR. As for biochar, the knowledge gaps are even greater. In the second part of this research, after the production and characterization of the biochar derived from DWT sludge, it was found that the increase in temperature negatively affected the biochar yield, which decreased from 37.5 to 33.5% as the temperature increased from 450 to 600°C. The dried sludge sample had a pH of 5.6 and, as the pyrolysis temperature increased from 450 to 600 ºC, the pH of the biochar increased from 6.6 to 6.9. BC600, produced at a higher temperature, had a larger surface area (66.54 m²/g) than BC450 (43.18 m²/g). After chemical activation, the activated biochar (BC600A) showed a substantial increase in surface area, reaching 2,000 m²/g. Furthermore, chemical activation resulted in a decrease in the zeta potential. The high mineral fraction in the sludge resulted in biochar rich in ash (61-71%) and low in carbon (0.2-1.4%), thus attributing more inorganic than organic characteristics to the material. The biochar produced at a higher temperature showed a more developed carbonaceous structure typical of adsorbent materials. Finally, the application of biochar in the treatment process proved inefficient for the treatment of natural waters, having little contribution to the coagulation and adsorption process. Thus, the use of DWT sludge biochar should be studied further to better understand its characteristics and possible chemical or physical modifications that could improve its properties as an adsorbent.